A Physische Geographie de Immanuel Kant: descrição e história da natureza - Antonio Carlos Vitte (Confins)
This article seeks to relate Kantian geography and philosophy. In one hand, for Kant geography is the only science that enables empirical and transcendental work due to the multiscale relationship according to the geographical description and to the history of nature that reconstructs the processes and landscapes of the past and also provides explanations for the landscapes today.